2021
DOI: 10.3389/fmed.2021.731214
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Pathway in Kidney Renal Clear Cell Carcinoma and Its Prognostic Value for Cancer Risk Prediction

Abstract: Angiogenesis, a process highly regulated by pro-angiogenic and anti-angiogenic factors, is disrupted and dysregulated in cancer. Despite the increased clinical use of angiogenesis inhibitors in cancer therapy, most molecularly targeted drugs have been less effective than expected. Therefore, an in-depth exploration of the angiogenesis pathway is warranted. In this study, the expression of angiogenesis-related genes in various cancers was explored using The Cancer Genome Atlas datasets, whereupon it was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To elucidate the correlation between TP53I11 and vascular endothelial cells, we employed the Lung Tumor ECTax database [ 28 ], a robust resource facilitating the exploration of gene expression within endothelial cell subtypes. Utilizing the clustering and grouping annotations from the original author, we reconfigured visualizations to depict the distribution of vascular endothelial cell subtypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the correlation between TP53I11 and vascular endothelial cells, we employed the Lung Tumor ECTax database [ 28 ], a robust resource facilitating the exploration of gene expression within endothelial cell subtypes. Utilizing the clustering and grouping annotations from the original author, we reconfigured visualizations to depict the distribution of vascular endothelial cell subtypes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, notably, KIRC exhibited a more favorable prognosis. Che et al conducted bioinformatics research to explore the relationship between angiogenesis-related genes and KIRC [ 28 ]. They observed that, unlike in other tumors (such as UCEC and KICH), most angiogenesis-related genes in patients with KIRC acted as protective factors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are responsible for catalyzing the elimination of acetyl groups from histone and non-histone lysine residues and are intimately linked to tumor onset and metastasis ( 18 ). Recently, suppression of HDAC has emerged as a method that has been verified in clinical practice for treating cancer ( 19 ). The levels of expression of HDAC1, HDAC7, and HDAC9 were found to be considerably lowered in C2 contrasted with the levels observed in C1 ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…It is critical to explore the potential predictor for KIRC treatment and prognosis. Angiogenesis is a complex consequence of co-regulation between pro-angiogenic and anti-angiogenic factors, and it is disrupted and dysregulated in cancer ( 33 ). Angiogenesis is an important process in cancer pathogenesis and therapy.…”
Section: Discussionmentioning
confidence: 99%